Book Reviews (Journal of Finance, 1985)
Book reviewed in this article: Capital Budgeting Techniques . By F.M. WILKES. New York: John Wiley & Sons, Second Edition, 1983. Pp. xii + 409. Management of Financial Institutions . By BENTON GUP. Boston, Massachusetts: Houghton Mifflin Co., 1984. Pp. 530. The Money Bazaars: Understanding the Banking Revolution Around Us . By MARTIN MAYER. New York: E. P. Dutton, Inc., 1984. Pp. 385. $22.50.